Economic feasibility of trigeneration plants for various prime movers and triple load demands. (June 2017) - Hajabdollahi, Hassan; Hajabdollahi, Zahra
In this paper, after thermal and economic modeling of cogeneration plant, this system is optimized to find the optimal prime mover and their benefit for various cooling, heating, and electrical demand loads. To find the optimal prime mover and their benefit for each triple load, two new nondimensional design parameters including electric cooling ratio and nominal power ratio are defined. It is observed that, for example, for higher electrical and lower heating load demands, the gas engine is more profitable while for higher electrical and heating load demands, diesel engine is more profitable. In addition, some ranges of demand loads at which using CCHP plant is not profitable (in comparison with traditional system) are also obtained and presented. The optimum results obtained in NO SELL mode show that the highest values of actual annual benefit (AAB) are obtained for highest values of electrical load demand. This region corresponds with values of Hdmn / Qdmn (heating to cooling load demand ratio) in the range of 1.5–3.5. The highest values of AAB for SELL mode are obtained to be in the range of 0.5–3.5 for Hdmn / Qdmn (heating to cooling load demand ratio).